Players and Arenas : The Interactive Dynamics of Protest - Duyvendak, Jan Willem; Jasper, James M., 1957-; Project Muse. (Amsterdam : Amsterdam University Press, 2015)
Players and Arenas brings together a diverse group of experts to examine the interactions between political protestors and the many strategic players they encounter, such as cultural institutions, religious organizations, and the mass media--as well as potential allies, competitors, recruits, and funders. Discussing protestors and players as they interact within the arenas of specific social contexts, the essays show that the main constraints on what protestors can accomplish come not from social and political structures, but from other players with different goals and interests. Through a careful treatment of these situations, this volume offers a new way to approach the role of social protest in national and international politics.
12. What the Tea Party and Occupy Wall Street Illuminate about Bystander Publics as Proto-Players Conclusion -- Contributors -- Index
English.
Description based on print version record.
Keywords: Interactie; Protestbewegingen; Social movements -- Psychological aspects; Protest movements; Political participation; SOCIAL SCIENCE -- Reference; SOCIAL SCIENCE -- Essays; Society and social sciences Society and social sciences; Politics and government; Political activism; Demonstrations and protest movements; Participation politique; Contestation; Mouvements sociaux -- Aspect psychologique; Political participation; Protest movements; Social movements -- Psychological aspects; Electronic books